2000
DOI: 10.1055/s-0037-1613828
|View full text |Cite
|
Sign up to set email alerts
|

Minor Events and the Risk of Deep Venous Thrombosis

Abstract: Backgtound Deep venous thrombosis is a common disease, with genetic and acquired nsk factors Many patients have a history of minor events (short penods of iramobihsaüon such äs prolonged travel, short illness. ramor surgery or injunes) before onset of venous thrombosis However. the role of these mmor events has received httle formal study Also, we do not know how mmor events might mteract with the presence of genetic prothrombotic defects (factor V Leiden mutation factor II mutation, protein C S and antithromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…A 30 day period of increased risk has been assumed previously, and a recent study reported a median interval of two days (range 1-14) between a trigger event and subsequent thrombosis 16. We examined the risk over intervals up to 30 days, using a model that allowed different incident rate ratios in three successive periods after travel, and we concluded that most of the excess risk was captured in the two weeks after a flight.…”
Section: Participants and Methodsmentioning
confidence: 91%
“…A 30 day period of increased risk has been assumed previously, and a recent study reported a median interval of two days (range 1-14) between a trigger event and subsequent thrombosis 16. We examined the risk over intervals up to 30 days, using a model that allowed different incident rate ratios in three successive periods after travel, and we concluded that most of the excess risk was captured in the two weeks after a flight.…”
Section: Participants and Methodsmentioning
confidence: 91%
“…Research-based definitions of immobility due to bedrest differ, but a duration of 4 days seems reasonable. Minor forms of immobility, such as after minor surgery or injury, have also been linked to thrombosis risk (33).…”
Section: Immobilitymentioning
confidence: 99%
“…In studies [7][8][9]14 that focused on major injuries, an asymptomatic venous thrombosis was detected in 0.4% to 12% of the trauma patients, despite prescribed prophylaxis. One study 15 found a 3-fold increased risk of venous thrombosis after minor events. However, minor events included, among others, travel, minor surgery, and minor trauma, and no information regarding minor trauma alone was available.…”
Section: Commentmentioning
confidence: 99%